2011
DOI: 10.1108/00220411111124541
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of changes in learners' cognitive states during and following an information literacy teaching intervention

Abstract: Purpose The paper identifies the changes in cognition associated with becoming information literate, specifically, in relation to the evaluation of information. Additionally, it puts forward a model for a teaching and learning intervention that engages the learner and leads to higher order information literacy (IL) thinking. From a theoretical perspective the research integrates ideas from the fields of IL, teaching and learning, e-learning and information behaviour (IB). Design/methodology/approach Three inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 45 publications
(84 reference statements)
4
101
0
3
Order By: Relevance
“…The analysis presented here was part of a PhD study carried out by the first author and complements the pilot study Stephens, 2007a and2007b) and qualitative findings for the main study (Pope & Walton, 2009;Hepworth & Walton, 2009;Walton, 2010;Walton & Hepworth, 2011) previously reported. The purpose of this research was to determine whether a blended approach to delivering an information literacy learning and teaching intervention (a mix of face-to-face and online) could significantly enhance undergraduate's information discernment as measured through their assessed work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis presented here was part of a PhD study carried out by the first author and complements the pilot study Stephens, 2007a and2007b) and qualitative findings for the main study (Pope & Walton, 2009;Hepworth & Walton, 2009;Walton, 2010;Walton & Hepworth, 2011) previously reported. The purpose of this research was to determine whether a blended approach to delivering an information literacy learning and teaching intervention (a mix of face-to-face and online) could significantly enhance undergraduate's information discernment as measured through their assessed work.…”
Section: Introductionmentioning
confidence: 99%
“…Many writers in the field of e-learning have indicated that online discourse is a valuable learning tool (for example, McConnell, 2006;Mayes & DeFreitas, 2007). Furthermore, previously reported qualitative work (Walton & Hepworth, 2011) carried out indicated that students who were exposed to blended learning which included online collaborative learning (OCL), also known as online social network learning (OSNL) or the preferred term social media learning (SML), where more likely to use higher order cognitive skills such as analysis and synthesis (as defined by Bloom, Engelhart, Furst, Krathwohl & and Hill, 1956) when evaluating web sites. It is argued that this greater use of higher order skills might be observed by comparing assessed work, specifically students' ability to evaluate information (information discernment).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, critics of IL note that this instrumental nature found in the text of some of the older IL 'grand theories' (for example, Association of College & Research Libraries, 2000) are incompatible with the constructivist and critical approach they promote (Markless & Streatfield, 2007). Robust theoretical works (Fisher et al, 2005) and empirical studies (Hepworth, 2004) supported by extensive information behaviour research (such as, Walton & Hepworth, 2011;Bruce et al, 2013) on the cognitive, metacognitive, affective and social processes which underpin IL indicate that IL is less of an individualised activity and more social in nature. Lloyd (2012), in particular, has shown that IL is more akin to a socio-cultural or socially-enacted practice.…”
Section: Introductionmentioning
confidence: 99%
“…As Bandura (1977) stipulated, skills in themselves are not necessarily enough, learners also need to have confidence in the abilities they are developing. Nationally the House of Lords makes their intentions for learners clear in that they aim to deliver 'a cultural shift towards preparing learners to learn for themselves ' (p.12, House of Lords, 2015); however, despite this there have been few investigations into the psychosocial, social and cognitive effects of Information Literacy (Kumar andEdwards 2013, Walton andHepworth, 2011).…”
Section: '… Their Apparent Facility With Computers Disguises Some Wormentioning
confidence: 99%
“…The reality of interacting with information in a digital landscape is complex, uncertain and much more demanding than previous landscapes which traditionally consisted of mediated information resources (Connaway et.al., 2013). The future for these children and young people 'will be characterised by an increasingly complex and constantly evolving information landscape' (Coombs, 2013) which requires a level of cognitive interaction that goes beyond the use of digital tools and becomes a metacognitive activity of self-regulation (Walton and Hepworth, 2011).…”
Section: Introductionmentioning
confidence: 99%